2014
DOI: 10.1542/peds.2012-2537
|View full text |Cite
|
Sign up to set email alerts
|

Meglitinide Analogues in Adolescent Patients With HNF1A-MODY (MODY 3)

Abstract: For pediatric patients with hepatocyte nuclear factor-1A (HNF1A)-maturity-onset diabetes of the young (MODY 3), treatment with sulfonylureas is recommended. In adults with HNF1A-MODY, meglitinide analogues achieve lower postprandial glucose levels and pose a lower risk of delayed hypoglycemia compared with sulfonylureas. This therapy has not yet been reviewed in pediatric patients. We report on meglitinide analogue treatment in 3 adolescents with HNF1A-MODY. Case 1 (14-year-old girl) was diagnosed asymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 24 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…There is a published case report on the use of repaglinide and nateglinide in adolescents with HNF1A-MODY. In this study of three adolescents, use of meglitinides was associated with no or rare hypoglycemia compared to frequent hypoglycemia on SUs, suggesting that meglitinides could be the first-line therapy for adolescents with HNF1A-MODY, ahead of SUs [54]. …”
Section: Therapeutic Implications Of Diagnosing Monogenic Diabetes Inmentioning
confidence: 99%
“…There is a published case report on the use of repaglinide and nateglinide in adolescents with HNF1A-MODY. In this study of three adolescents, use of meglitinides was associated with no or rare hypoglycemia compared to frequent hypoglycemia on SUs, suggesting that meglitinides could be the first-line therapy for adolescents with HNF1A-MODY, ahead of SUs [54]. …”
Section: Therapeutic Implications Of Diagnosing Monogenic Diabetes Inmentioning
confidence: 99%
“…Sulphonylureas have been shown to successfully bypass the major β–cell defects that result in HNF1A–MODY . The response to sulphonylureas in individuals with HNF1A–MODY has been investigated in a number of small studies . The specific therapeutic response to sulphonylureas in HNF1A–MODY was confirmed by a double‐blind randomized clinical study comparing the efficacy of gliclazide and metformin in HNF1A–MODY and Type 2 diabetes mellitus .…”
Section: Introductionmentioning
confidence: 98%
“…Tuomi et al demonstrated in 15 HNF1‐α MODY patients that nonsulphonylurea secretagogue nateglinide at very low doses (30 mg) prevents acute postprandial rises of glycaemia more effectively than the reference drug glibenclamide; moreover, it did so with a lower incidence of hypoglycaemia during lower peak levels of stimulated insulin. A small study involving 3 adolescent HNF1‐α MODY patients reported comparable efficacy of glinides to the reference treatment with sulphonylurea derivatives and insulin, as well as good tolerance and a better safety profile with a significantly lower risk of hypoglycaemia …”
Section: Treatment Of Different Types Of Modymentioning
confidence: 99%